Mapping Curriculum Models in Contemporary Islamic Education: Comparative Analysis, Advantages and Implementation Challenges - Asykur, Muamar; M, Ratna; Hanna, Hanna (International Journal on Advanced Science, Education, and Religion, 2024)
Islamic education historically has had an existence and role in developing individuals who are physically and spiritually perfect. However, when looking at the implementation of Islamic education in institutional systems and educational systems, sometimes there are problems that hinder the education system from achieving its goals. Internal problems include the fact that, although Islamic education has been formally and theoretically evaluated, it has provided benefits to students who have fairly good intellectual abilities. However, students cannot automatically apply mastery of the cognitive domain in their actions or deeds. A qualitative approach will be used in this research through literature study, in-depth interviews with experts and practitioners, observations at Islamic educational institutions, as well as case studies at several institutions that implement different curriculum models. Research Results Show By considering the challenges facing Islamic education, the curriculum must be designed to share knowledge and values, not only quantitative knowledge, but also to produce quality output that is resistant to developments over time. Quality education is defined as education that is able to develop the potential of the education system and components in a way that is not only in quantity but also capable of producing output that is resistant to developments over time.